Comparative Analysis of the Effectiveness of Manual Toothbrushes in Maintaining Oral Hygiene During Fixed Orthodontic Treatment - Dr. Anna George Palatty, Dr. Shikha Singh, Dr. Madhubala Yadav, Dr. Kajal Dokarimare, Dr. Akanksha Sharma, Dr. Vedika Mallik, Dr. Pulkit Sharma (South Eastern European Journal of Public Health, 2025)
Fixed orthodontic treatment increases the risk of plaque accumulation, gingival inflammation, and enamel decalcification, making oral hygiene maintenance crucial. This study aimed to compare the effectiveness of different manual toothbrushes flat bristles, criss-cross bristles, and zig-zag bristles in reducing plaque scores among orthodontic patients over 60 days. A total of patients undergoing fixed orthodontic treatment were divided into three groups based on the toothbrush type used. Plaque scores were recorded at baseline, 30 days, and 60 days using standardized indices. Results showed that at baseline, no significant differences were observed among the groups (p > 0.05). However, after 30 days, significant improvements were noted in the criss-cross (p = 0.004) and zig-zag bristle groups (p = 0.016), while the flat bristle group did not show a statistically significant reduction (p = 0.083). By 60 days, all groups exhibited significant improvements, with the criss-cross bristle toothbrush demonstrating the greatest reduction in plaque scores (mean difference = 1.85, p = 0.000), followed by the zig-zag bristle toothbrush (mean difference = 1.35, p = 0.000), and the flat bristle toothbrush (mean difference = 1.75, p = 0.000). Pairwise comparisons revealed that the criss-cross bristle toothbrush consistently outperformed the flat bristle toothbrush across all time points. These findings indicate that while all toothbrushes contributed to improved oral hygiene over time, criss-cross bristle toothbrushes were the most effective in reducing plaque accumulation in orthodontic patients. The study highlights the importance of selecting an appropriate toothbrush for maintaining optimal oral hygiene during orthodontic treatment.